Rebel Recruitment and Migration: Theory and Evidence From Southern Senegal - Max Schaub; Daniel Auer (Journal of Conflict Resolution, 2022)
We investigate whether the threat of recruitment by rebel groups spurs domestic and international migration. The existing literature on wartime displacement has largely focused on potential victims of violence. We argue that alongside potential victims, we should expect to see the out-migration of individuals who are attractive to the rebels as potential recruits. To test this hypothesis, we draw on original survey data collected in the context of the MFDC insurgency in southern Senegal. Causal identification stems from instrumenting recruitment threat with the density of the local forest canopy cover. Analyzing data from 3,200 respondents and over 24,000 family members, we show that individuals who fit the recruitment profiles of rebel groups are more likely to leave and be sent away by their families. Our paper contributes micro-evidence for a mechanism linking violent conflict to migration, which so far has received scant attention, and provides a deeper understanding of the composition of refugee flows.
doi:10.25384/SAGE.20555996.v1
Keywords: 320; rebel recruitment; insurgency; migration; displacement; Senegal